The influence of sodium and leukocyte levels as predictor factors in pediatric perforated appendicitis at bhayangkara tk. i pusdokkes police hospital - Garba Sandhi Wusana Despriyatmoko; Sumidi Sumidi (Science Midwifery, 2023)
Acute appendicitis is an inflammation of the appendix, the part of the small intestine located in the lower right side of the abdomen. This is a severe medical condition that usually requires surgery emergency. The main symptoms of acute appendicitis include abdominal pain radiating to the lower right side, fever, and nausea. This study aims to determine the role of sodium and leukocytes as predictors of perforated appendicitis in children at Bhayangkara Tk. I Pusdokkes Police Hospital. This concept is expected to help the readers understand how sodium level and leukocyte count can predict the likelihood of children's perforated appendicitis. This study is important for improving the diagnosis and treatment of children with perforated appendicitis. The study's results through a total sample of 52 participants showed significant differences in sodium and leukocyte levels in patients with a diagnosis of perforated appendicitis and appendicitis without perforation. This was proven by the results of testing using the Mann-Whitney differential test, which obtained a significance value for Na levels of 0.049 and leukocyte levels of 0.000. These values were smaller than the p-value of 0.05. The accuracy of the diagnosis of leukocyte levels is shown through two AUC values (Area Under the Curve) of 0.747 or 74.7%. This value is greater than 70% and indicates very good accuracy. Meanwhile, the AUC value for sodium levels is only 0.229 or 22.9%, so it is considered less accurate. The Cut Off value for Na levels was 132.50 mEq/liter, while leukocytes were 13.715/microliter of blood.